Global carbon recoverability experiences from the cement industry - Mugahed Amran; Natt Makul; Roman Fediuk; Yeong Huei Lee; Nikolai Ivanovich Vatin; Yee Yong Lee; Kachalla Mohammed (Case Studies in Construction Materials, 2022)
Achieving net-zero emissions requires rapid decarbonization and improved strategies implemented at the global level. In response to increasing demand for better structures and foundations, the concrete industry now relies on heating furnaces to over 1400 °C by burning fossil fuels and other cementitious materials, accounting for about 7–8% of carbon emissions. Even though the timeframe set by the Paris Agreement by United Nations (UN) to radically limit carbon emissions and improve carbon recovery is relatively short, i.e., countries reduce their Greenhouse Gas emissions to 'net zero' by around 2050, it still exceeds the time it has left to avoid the worst effects of global warming. Empirical evidence suggests that the management of carbon in the Earth’s ecosystems is still in the hands of humans and that effective strategies can be employed to restore carbon stocks and achieve net-zero emissions. This paper considers carbon emissions and recoverable carbon from a global perspective to identify the sources of CO2 emissions, the status of CO2 recovery strategies and implementation, and practical strategies to improve CO2 recovery in Portland cement production. A literature review shows that several decarbonization pathways have been adopted to manage CO2 recovery, namely alternative materials, fossil fuel substitution, and carbon capture and storage (CCS). However, no carbon recovery pathway sufficient to achieve net-zero emissions has been identified. Therefore, a comprehensive study of the Portland cement industry and CO2 recoverability is needed to fully quantify carbon emissions and establish optimum strategies in terms of sustainability, cost-effectiveness, and business climate supported by strong political policies and associated regulations.